Implementation of Decision Support System for Analyzing the Suitability of Plantation Crops - Fitri, Zilvanhisna Emka; Irawan, Ahmad Dandi; Madjid, Abdul; Imron, Arizal Mujibtamala Nanda (Universitas Multimedia Nusantara, 2025)
The productivity of plantation crops is a priori dependent on the suitability of the land and the quality of the land used. The objective of determining land suitability is to increase the amount of crop production, thereby preventing crop failure. The process of land evaluation entails the assessment of land performance with the objective of predicting the potential and limiting factors for crop production. This allows for the identification of alternative types of agriculture. The application of the Fuzzy Mamdani method to the land suitability assessment website, based on rainfall parameters, soil pH and planting depth, is able to provide a land class assessment while making recommendations for plantation crops as an alternative type of agriculture.